Evaluation of layer adhered on PCBN tools during turning of AISI D2 steel. (November 2019) - Sirtuli, Larissa Juliana; Boing, Denis; Schroeter, Rolf Bertrand
Abstract: Polycrystalline cubic boron nitride (PCBN) tools have high abrasion resistance and are thus suitable for application in the machining of steels with a high volume fraction of primary carbides in their microstructure. These tools are usually applied in the machining of steels with hardness above 45–50 HRC and in the case of application to steels with hardness below 45 HRC, the formation of an adhered layer on the rake face of the tools often occurs. This paper reports a study on the impact of the layer adhered on PCBN tools during the turning of AISI D2 steel, with 35 and 50 HRC. The microhardness and microstructure of the adhered material were determined, as well as the tool wear based on volumetric wear parameters. The layer adhered on the PCBN tool rake face has the same chemical elements as the machined steel alloy. Its microstructure is oriented in the direction of the chip flow and the primary carbides were fragmented. For the sample with 35 HRC the amount of material adhered (WAM ) on the rake face of the PCBN tool was approximately 360% higher than the steel with 50 HRC. The material layer adhered on the PCBN tool rake surface in the case of the 35 HRC steel acts as an edge (assuming the cutting function), while for the 50 HRC steel, the adhered layer intensifies the adhesion wear mechanism through spalling on the tool rake face. The results obtained provide important information for the selection of materials and grades for the development of new cutting tools. Highlights: Microstructure and hardness characterization of the layer adhered on PCBN tools. Mechanisms of PCBN tool wear in the turning of AISI D2 with middle hardness value (35‐50 HRC). The revelation of adhesion wear mechanism on the PCBN tool. Machining process evaluated by three-dimensional (volumetric) tool wear parameters.